(untitled) (Indian Journal of Public Health Research & Development, 2024)
ABSTRACT: Diabetes Mellitus causes a global burden due to its systemic complications that affect different parts of the body especially eye. DR is a common micro vascular complication of DM, and which causes significant visual impairment and blindness worldwide. Hence, regular screening of the eye is mandatory to prevent visual impairment and blindness due to Diabetic Retinopathy Aims/Objectives: The Objective of the study is to assess the level of awareness and practices among the study participants attending Non Communicable Disease OPD at Tertiary Care centre. Methodology: The study period was six months from January 2021 to June 2021 with a sample size was 300. The study tool was Semi- structured Questionnaire to assess the level of awareness and practices among the study participants attending Non Communicable Disease OPD at Tertiary Care centre. Chi-square test was used for statistical analysis. p value Less than 0.05 was fixed as significant value. Results: A total of 300 participants 136 (45.3%) females and 164 (54.7%) males with Type 2 diabetes were interviewed. 281(93.7%) of the study participants knew that diabetes can have an impact on the eyes, and 207(69%), said that diabetic retinopathy can result in blindness. 231(77%) of the study population are well aware that the good diabetic control prevent diabetic retinopathy. 106 (35.3%) of the population visit for an annual eye checkups. Very minimal population 25(8.3%) undergoes eye check-up when newly diagnosed as DM. Conclusion: Preventive measures should be taken to create awareness among diabetic patients and also the general population